2004
DOI: 10.1001/archsurg.139.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment for Primary Hyperparathyroidism in Hong Kong

Abstract: Hypothesis: With the introduction of the blood chemistry multichannel autoanalyzer, primary hyperparathyroidism (HPT) is increasingly diagnosed. The clinical pattern of primary HPT has undergone a significant evolution in Western countries. A similar change can be documented in a geographic region where this condition is considered to be relatively uncommon. Design: Unselected case series. Setting: A tertiary referral endocrine surgical unit. Patients: All patients with primary HPT surgically treated over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 16 publications
6
23
1
Order By: Relevance
“…Others have reported similar experiences regarding trends in preoperative serum calcium and/or adenoma weight [2,3,5], and adenoma weights in our series were similar to those in contemporary reports [10][11][12] but lower than in earlier series [13]. It is probable that the observed decrease in adenoma weight and preoperative serum calcium levels indicate that patients are operated at an earlier stage of the disease.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Others have reported similar experiences regarding trends in preoperative serum calcium and/or adenoma weight [2,3,5], and adenoma weights in our series were similar to those in contemporary reports [10][11][12] but lower than in earlier series [13]. It is probable that the observed decrease in adenoma weight and preoperative serum calcium levels indicate that patients are operated at an earlier stage of the disease.…”
Section: Discussionsupporting
confidence: 88%
“…This is contrary to what was found in the study by Lo et al where PTH levels decreased from a mean of 342 pg/ml in 1983-1992 to 155 pg/ml in 1993-2002 [5]. An intriguing explanation could be that the PTH levels reflect adenoma in evolution.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In Rochester, Minnesota, the total incidence of pHPT treated at theMayo Clinic decreased since its peakin1974-1982; however, the number of parathyroidectomies performed increased over the same period of time at that institution [5]. Outside the U.S., a Hong Kong study found a sevenfold increase in operative pHPT over the past decade [6], in Denmark the diagnosis of pHPT has increased fivefold in women and threefold in men over the past 20 years [7], and in China the percentage of patients with pHPT who were asymptomatic at the time of their diagnosis has increased from ,21% to 52.5% over 10 years [8].…”
Section: Introductionmentioning
confidence: 99%
“…(Bilezikian et al 2000;Lo et al 2004;Chen et al, 2010) In contrast, in the Western world, pHPT is a relatively more common disease with an estimated incidence of 42 to 190/100,000 cases per year. Surgical treatment or parathyroidectomy remains the only curative therapy for patients with pHPT.…”
Section: Introductionmentioning
confidence: 99%